Russian Orthodox Churches in Birlya and Taburnoe Villages of the Ulyanovsk Oblast - Evgeniy A. Burdin; Kirill V. Safin (Publishing house "Sreda", 2021)
The article reflects the results of research on the topic «History and cultural heritage of the settlements of the Ulyanovsk region." The subject of the research is the history of the St. Michael the Archangel's Church and the Kazan-Mother of God church in the villages of Birlya and Taburnoe (now belonging to Melekessky district of the Ulyanovsk region). The purpose of the article is to identify the most important periods of the above-mentioned churches from the end of the 19-th century to the 1950-s, to establish the composition of the clergy, and the educational work of the clergy among the population. Analysis of unpublished documents from the Central State Archives of the Samara Region allowed to establish: the ethnic composition of the settlements, socio-economic status of inhabitants, reasons and patterns of migration of the local population; the foundation and liquidation dates of the churches, facts of life of church ministers and parish; statistical data on the economic structure of the clergy. The Mikhailo-Arkhangelsk and Kazan-Mother of God churches in the villages of Birlya and Taburnoye are lost monuments of the Orthodox cultural heritage. Mikhailo-Arkhangelsk and Kazan-Mother of God churches were built, respectively, at the end of the 19th century. and destroyed in the first half of the 1950-s. in connection with the construction of the Kuibyshev hydroelectric power station, and their location is flooded by a reservoir.